Prinsip Penggunaan Tertinggi dan Terbaik Untuk Menentukan Jenis Pemanfaatan Lahan Pasar - Wijaya, Agus; Setiawan, Putu Rudy (Journal of Regional and City Planning, 2008)
A piece of land located strategically in the downtown of Bulukumba City covering 11.440 sq meters, owned by Bulukumba Regency, has been left unoccupied for more than 8 years. The land is formerly occupied by Bulukumba central market which was relocated 8 years ago. Since then the land was remain unmanaged and no effort has never been made to develop it for instance by permitting generating income activities or even social activities to exploit the land. The paper aims to determine the best use of that piece of land. The best land use is obtained by employing Highest and Best Use Method. This kind of method needs land market value as indicator assuming that the highest value reflects the best use of land. The highest land value for specific kind of land use is obtained by involving land residual technique and cash flow method. The result will then be compared by the land value for the same land in vacant condition by using direct market comparison method. The research concludes that the highest and best use of the land, which formerly used for central market in Bulukumba city, is shopping centre. This kind of land use may create market land value as high as Rap. 2.000.000,-/m².